Learning-by-Doing in Dynamic General Equilibrium Models: Macroeconomic Implications and Estimates - Clarke, Andrew J. (My University, 2004)
This thesis develops and estimates a structural model in which organizations, engaged in the process of production, acquire knowledge that raises their productivity. This knowledge is treated as an organization specific capital good, that is jointly produced with output and embodied in the organization itself. This organizational capital is accumulated subject to an accumulation technology that implies production units faces a trade-off between maximizing current period profits and losing future productivity increases. This thesis shows that this dynamic structure, which has previously been ignored in existing studies of learning-by-doing, might have important economic implications. The results presented in this thesis contribute to our knowledge of the macroeconomic effects associated with the accumulation of organizational capital by focusing exclusively upon the accumulation of organizational capital by production units. This thesis establishes that when production experience is accumulated and stored by production units the implied values of several key macroeconomic variables in the non-stochastic steady state will be quite different to those implied by an otherwise identical model that ignores the accumulation of organizational capital. It is also shown that the accumulation of organizational capital generates a hump-shaped dynamic response of output to a fiscal policy shock. This hump-shaped output response is an important feature of the empirical dynamic responses. More importantly, a model that ignores organizational capital is unable to produce dynamic responses in output and investment that exhibit this hump-shaped response. Consequently, the dynamic responses associated with the accumulation of organizational capital might be consistent with the stylized facts associated with the empirical responses. These results suggest that the accumulation of production experience by production units will likely to be an important component of the endogenous propagation mechanism identified by Cooper & Johri (2002). These macroeconomic effects arising from the accumulation of organizational capital rely critically upon the existence of a dynamic structure, at the plant level, associated with the accumulation of organizational capital. The results presented in this thesis suggest that this dynamic structure will be empirically important for production units across a diverse range of (manufacturing) industries. Consequently, existing studies of learning-by-doing that aim to quantify the productivity of (accumulated) production experience without also considering the (endogenous) accumulation of this production experience are likely to be seriously flawed.
Keywords: Economics; Economics